β-Adrenergic Blocking Agents and Intermittent Claudication: Systematic Review - MIYAJIMA, Ritsuko; YOSHIDA, Hisahiro; SANO, Kazumi (YAKUGAKU ZASSHI, 2004)
To clarify contradictions in past reports and the package inserts for β-adrenergic blocking agents (β-blockers) for patients with intermittent claudication (IC), we investigated the effects of β-blockers in patients with IC using the systematic review technique. Data sources were randomized, controlled trials that investigated the effects of β-blockers compared with the placebo or untreated group (controls) in patients with IC. Primary endpoints were walking distance and walking time, and secondary endpoints were ankle-brachial index (ABI) and calf blood flow. Nine trials were included in the analysis. Meta-analysis showed that there was a significant worsening in maximal walking distance and initial claudication distance in patients receiving β-blockers, with standardized mean differences of -0.31 and -0.39 (95% confidence interval -0.58 to -0.04 and -0.73 to -0.06, P=0.03 and 0.02, respectively) compared with controls. There were no significant differences in maximal walking time (0.07, -0.24 to 0.37), time to onset of claudication (0.12, -0.23 to 0.47), ABI at rest (0.24, -0.30 to 0.78), calf blood flow at rest (0.00, -0.26 to 0.25), and calf blood flow after exercise (-0.23, -0.69 to 0.22). However, only one trial evaluated ABI, and the number of cases is increasing, suggesting that β-blockers do not worsen ABI. There was no evidence that β-blockers prescribed for patients with IC have unsuitable “precautions” in the package inserts. However, reluctance to administer β-blockers to patients because they have IC is not appropriate.